Features the interaction of functional and metabolic remodeling of myocardium in comorbid course of ischemic heart disease and 2 type diabetes mellitus - Sergey A. Afanasiev (Endocrinology Research Centre, 2019)
Background: Metabolic and structural changes in cardiomyocytes in diabetes mellitus lead to aggravation of contractile myocardial dysfunction in coronary heart disease (CHD). The contractility dysfunction of cardiomyocytes is determined by a change in the levels of sarcoplasmic reticulum (SR) Ca2+-ATPase and energetic supply of the cardiomyocytes. Aims: To study the features of functional remodeling of the heart muscle in coronary heart disease with and without type 2 diabetes mellitus (DM2) depend on the level of Ca2+-ATPase and the activity of enzymes involved in energy metabolism. Materials and methods: The work was performed on the heart biopsy of patients with CHD and patients with CHD combined with DM2. The inotropic reaction of myocardial strips on rest periods was assessed. The expression level of Ca2+-ATPase, the activity of enzymes succinate dehydrogenase (SDH) and lactate dehydrogenase (LDH) and the intensity of oxidative phosphorylation processes were determined. Results: The interval-force relationship in patients with CHD with and without DM2 had both negative and positive dynamics. The positive dynamics corresponds to the "high content" of the Ca2+-ATPase and the negative dynamics corresponds to the "low content" were found. At the combined pathology the positive inotropic dynamics is more pronounced and corresponds to a higher protein level. In the patients myocardium with CHD the activity of SDH and LDH was higher, while the oxygen uptake rate by mitochondria was higher in the myocardium with combined pathology. Conclusions: The potentiation of inotropic response of patient myocardium with CHD with and without DM2 corresponds to the "high level" of Ca2+-ATPase. In the combined pathology the inotropic capabilities of the myocardium are more expressed. In CHD the synthesis of ATP in cardiomyocytes is realized mainly due to glycolytic processes and Krebs cycle. In combined pathology the ATP synthesis is realized to a greater extent due to the oxidative phosphorylation.